Application of Decision Theory Methods in Vehicle Creation (Current Problems in Rail Vehicles, 2021)
The level of effective bogie work is determined and evaluated according to a large number of monitored parameters because the influence of these factors in different modes of rolling stock is different. The aim of the present study is to determine the appropriate way of decision-making in the creation of rolling stock and with its help to identify the factors that have the most significant impact on the efficiency of the rolling stock. An objective function has been created that allows the selection of the most efficient technical solution from a number of alternatives. The effectiveness of the selective selection of traction electric motor (TEM) characteristics for two-wheelers is considered, taking into account the load redistribution and the difference in adhesion.
Keywords: objective function; traction force; torque; vertical load